Discordance in the paraoxonase (Pon1)-192QR polymorphism - Poh, R.; Muniandy, S. (2008)
Paraoxonase (PON1) has been implicated to have a cardioprotective role, due to its physical attachment with high-density lipoprotein. PON1192QR is a variation of the PON1 gene, the R allele being a risk factor for cardiovascular disease. Kinetic studies resulting in a plot of paraoxon versus diazoxon hydrolysis rates may be used to accurately predict PON1192 geno-type. In this study, paraoxonase and diazoxonase activities in plasma were measured spec-trophotometrically using plasma while PCR-based PON1192 genotyping was performed us-ing polymerase chain reaction followed by restriction digestion. The two-substrate assay-derived genotypes were cross-referred with those determined by PCR-based genotyping. When results did not concur, sequencing of the 99-bp region spanning codon 192 of PON1 was performed to verify the genotype. Concordant samples with high or low activities were sequenced for comparison. In addition, the rare PON1194WX polymorphism was examined as a source of discordance. The frequency of the PON1192Q allele in a Malaysian population comprising three ethnic groups (Malays, Chinese and Indians) was estimated to be 0.46, and that of the PON1192R allele, 0.54. Discordance between the genotype and phenotype was ob-served for two samples. One of the two subjects genotyped as PON1192QR and phenotyped as PON1192QQ. The sample showed low paraoxonase and diazoxonase activities. Sequencing confirmed that the genotype was PON1192QR. The other subject was genotyped as PON1192RR but phenotyped as PON1192QR. Sequencing showed that the genotype was in fact PON1192RR, with the subject showing relative high activities. The PON1194WX mutation was not detected in the sequenced samples and was not the source for discordance.